2008
DOI: 10.1080/10584580802558043
|View full text |Cite
|
Sign up to set email alerts
|

SYNTHESIS AND CHARACTERIZATION OF SB-SUBSTITUTED (K0.5Na0.5)NbO3 PIEZOELECTRIC CERAMICS

Abstract: Lead-free piezoelectric ceramics (K 0.5 Na 0.5 )(Nb 1−x Sb x )O 3 +0.5 mol.%MnO 2 , where x = 0 ÷ 0.10, with single phase structure and rhombohedral symmetry at room temperature were prepared by conventional ceramic technology. The optimal sintering temperatures of compositions were within 1100 • -1140 • C. MnO 2 functions as a sintering aid and effectively improves the densification. The samples reached density from 4.26 g/cm 3 for undoped (K 0.5 Na 0.5 )NbO 3 to 4.40 g/cm 3 for Mn/Sb 5+ co-doped ceramics. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…Generally, the piezoelectric coefficient d 33 can be improved at the expense of lowing T C and vice versa. Among the large number of KNN‐based lead‐free materials, d 33 can be improved by moving T O‐T or T R‐T to room temperature by various chemical substitutions, such as 0.948KNN‐0.052LiSbO 3 , 0.99KNN‐0.01BiFeO 3 , and (K 0.5 Na 0.5 )(Nb 0.93 Sb 0.07 )O 3 , however, the T C is decreased at different magnitude. Here, the present composites of KNN: x ZnO exhibit enhanced piezoelectric coefficient d 33 but with well‐maintained high T C .…”
Section: Resultssupporting
confidence: 66%
“…Generally, the piezoelectric coefficient d 33 can be improved at the expense of lowing T C and vice versa. Among the large number of KNN‐based lead‐free materials, d 33 can be improved by moving T O‐T or T R‐T to room temperature by various chemical substitutions, such as 0.948KNN‐0.052LiSbO 3 , 0.99KNN‐0.01BiFeO 3 , and (K 0.5 Na 0.5 )(Nb 0.93 Sb 0.07 )O 3 , however, the T C is decreased at different magnitude. Here, the present composites of KNN: x ZnO exhibit enhanced piezoelectric coefficient d 33 but with well‐maintained high T C .…”
Section: Resultssupporting
confidence: 66%
“…The main problem with KNN is sintering: it is difficult to obtain well-sintered KNN ceramic using an ordinary sintering process because of the high volatility of alkaline elements at high temperatures [6]. To produce well sintered, dense ceramic with one phase there was added 0.5 mol % MnO 2 as sintering aid.…”
mentioning
confidence: 99%
“…24 Dambekalne and Antonova studied the (Na,K)(Nb,Sb)-MnO 2 system and found that MnO 2 functions as a sintering aid and effectively improves the densification. 25 Wu and Xiao researched the (Na,K)(Nb,Sb)-CaTiO 3 system; their results show that CaTiO 3modified (Na,K)(Nb,Sb) lead-free piezoelectric ceramics form a stable solution with an orthorhombic structure and that the piezoelectric properties of the ceramics strongly depend on the poling temperature. 26 Park and Seo investigated the 2% CuO doped in the (Na,K)(Nb,Sb) system.…”
mentioning
confidence: 99%